Impact of Emotional Intelligence and Spiritual Intelligence on Happiness with Mediating Effect of Mental Well-Being - Manish Sharma , Trapti Tak (Mathematical Statistician and Engineering Applications, 2022)
The present paper reveals life skills Covid-19 pandemic- the unwelcome guest of our country has an impact on the happiness of college going students. Many factors such as their social life, family income, and academic infrastructure and so on took a new shape. These putting together resulted in myriads of emotions, testing their mental well-being and questioning their pursuit of happiness. The situation though hapless, made the students work on their management of emotions and urged them to dive deeper into spirituality. Emotional intelligence, spiritual intelligence together with mental well-being is seen to promote happiness. Therefore, the purpose of the study was to investigate the relationship among these constructs with respect to college students in India. The study was done through purposive sampling technique using closed ended weighted mean, Pearson correlation, regression and Sobel’s mediation analysis were used for the study. Emotional intelligence, spiritual intelligence, mental well-being and happiness were significantly correlated. Mental well-being showed a mediation effect towards the relationship between emotional and spiritual intelligence in promoting happiness.